Effect of postharvest treatments with different sources of carbohydrate on quality and vase life of gerbera (Gerbera jamesonii Bolus ex. Hooker f.) cut flowers cv. Grandola - Karuppaiah, P (Journal of Postharvest Technology, 2022)
The postharvest study in gerbera cut flowers vv. Grandola was carried out with different sources of carbohydrate such as sucrose, common sugar,  palm crystals, palm sugar and karupatti each at 2, 4 and 6% to assess the quality attributes and vase life. The experiment was laid out in completely  randomized block design with 16 treatments and a control in three replications. The observations viz., cumulative water uptake, cumulative  transpirational loss of water, water balance, fresh weight of cut flower, cumulative physiological loss in weight, stem strength, diameter of the flower,  flower discoloration, freshness of flower, TSS, pH of vase solution and vase life were recorded to test the quality and vase life of gerbera cut flowers.  The result revealed that sucrose 4% was found to be the best vase solution and proved better in terms of vase life and its dependent parameters when  compared to control.
Keywords: Carbohydrates; common sugar; gerbera; karupatti; palm sugar; , palm crystals; postharvest treatments